Optical Microscopy Systems for the Detection of Unlabeled Nanoparticles - Friedrich, Ralf P.; Kappes, Mona; Cicha, Iwona; Tietze, Rainer; Braun, Christian; Schneider-Stock, Regine; Nagy, Roland; Alexiou, Christoph; Janko, Christina (International Journal of Nanomedicine, 2022)
Label-free detection of nanoparticles is essential for a thorough evaluation of their cellular effects. In particular, nanoparticles intended for medical applications must be carefully analyzed in terms of their interactions with cells, tissues, and organs. Since the labeling causes a strong change in the physicochemical properties and thus also alters the interactions of the particles with the surrounding tissue, the use of fluorescently labeled particles is inadequate to characterize the effects of unlabeled particles. Further, labeling may affect cellular uptake and biocompatibility of nanoparticles. Thus, label-free techniques have been recently developed and implemented to ensure a reliable characterization of nanoparticles. This review provides an overview of frequently used label-free visualization techniques and highlights recent studies on the development and usage of microscopy systems based on reflectance, darkfield, differential interference contrast, optical coherence, photothermal, holographic, photoacoustic, total internal reflection, surface plasmon resonance, Rayleigh light scattering, hyperspectral and reflectance structured illumination imaging. Using these imaging modalities, there is a strong enhancement in the reliability of experiments concerning cellular uptake and biocompatibility of nanoparticles, which is crucial for preclinical evaluations and future medical application
Keywords: label free imaging; nanoparticle detection; non-fluorescent imaging; reflectance imaging; holotomography; scattering microscopy